Physical punishment on children as the onset of challenging behaviour in primary schools, South Africa: A review of literature - Julie Shantone Rubbi Nunan (Perspectives in Education)
Learners’ challenging behaviour is a growing concern in primary schools. Reports reveal that many learners in South African primary schools are presenting with challenging behaviour - disrupting lessons, causing chaos, putting learners’ and teachers’ safety at risk, and interrupting school functionality. To understand this phenomenon, a systematic review of literature spanning three decades was conducted to determine whether physical punishment of children leads to the onset of challenging behaviour in primary schools. The social cognitive theory emphasised how children learn and replicate behaviour, and punished children can quickly adopt punishing behaviours themselves. Thematic analysis of forty-five research sources on the impact of physical punishment on children’s behaviour identified several primary types of challenging behaviours physically punished children displayed in primary schools. The review established a clear link between physically punished children and the manifestation of challenging behaviour in school settings. These results imply that physical punishment of children can be painful, and the types of challenging behaviour displayed in primary school result typically from physical punishment. These results further imply that physical punishment of children can lead to the onset of challenging behaviour in primary schools. Education stakeholders should consider the behaviours presented in this review to improve and change how they view, support and manage misbehaving children. This should encompass school curriculum and policy reform and practice, including the implementation of relevant intervention strategies such as the ‘15 key steps to support misbehaving learners: A teacher's guide to effective intervention’ as recommended by this research.